Polysulfone으로 Al(OH)₃를 고정화한 PSf-Al(OH)₃ 비드에 의한 불소 이온의 제거 특성 - 전진우(Jin-Woo Jeon); 이민규(Min-Gyu Lee) (Clean Technology, 20(1), 2014)
In this study, PSf-$Al(OH)_3$ beads were prepared by immobilizating aluminum hydroxide $Al(OH)_3$ with polysulfone (PSf). The removal experiments of the fluoride ions by PSf-$Al(OH)_3$ beads were conducted batchwise and the parameters such as pH, initial fluoride concentration, and coexisting ions were investigated. The maximum removal capacity obtained from Langmuir isotherm was 52.4 mg/g and the optimum pH region of fluoride ions was in the range of 4 to 10. The removal process of fluoride ions by PSf-$Al(OH)_3$ beads was found to be controlled by both external mass transfer at the earlier stage followed by internal diffusion at the later stage. The presence of coexisting anions such as $HCO_3{^-}$, $SO{_4}^{2-}$, $NO_3{^-}$, and $Cl^-$ had a negative effect on removal of fluoride ions by PSf-$Al(OH)_3$ beads. 본 연구에서는 폴리술폰(polysulfone, PSf)으로 알루미늄 수산화물(aluminum hydroxide, $Al(OH)_3$)을 고정화한 PSf-$Al(OH)_3$ 비드를 제조하였다. 제조한 PSf-$Al(OH)_3$ 비드에 의한 불소 이온 제거실험은 회분식으로 수행하였으며, pH, 초기농도, 공존이온과 같은 변수들의 영향을 살펴보았다. Langmuir 등온식으로 구한 불소 이온의 최대 제거량은 52.4 mg/g이었으며, 최적 pH 범위는 4~10이었다. PSf-$Al(OH)_3$ 비드에 의한 불소 이온의 제거과정은 전 단계에서 외부물질전달이 나중 단계에서 내부확산이 지배인 것을 알 수 있었다. 또한 PSf-$Al(OH)_3$에 의한 불소 이온의 제거에서 $HCO_3{^-}$, $SO{_4}^{2-}$, $NO_3{^-}$, $Cl^-$와 같은 공존 음이온들은 불소 이온의 제거에 방해를 하는 것으로 나타났다.